EjRAV1/2 Delay Flowering Through Transcriptional Repression of EjFTs and EjSOC1s in Loquat - Peng, Ze; Wang, Man; Zhang, Ling; Jiang, Yuanyuan; Zhao, Chongbin; Shahid, Muhammad Qasim; Bai, Yunlu; Hao, Jingjing; Peng, Jiangrong; Gao, Yongshun; Su, Wenbing; Yang, Xianghui (Frontiers in Plant Science, 2021)
Most species in Rosaceae usually need to undergo several years of juvenile phase before the initiation of flowering. After 4-6 years’ juvenile phase, cultivated loquat (Eriobotrya japonica), a species in Rosaceae, enters the reproductive phase, blooms in the autumn and sets fruits during the winter. However, the mechanisms of the transition from a seedling to an adult tree remain obscure in loquat. The regulation networks controlling seasonal flowering are also largely unknown. Here, we report two RELATED TO ABI3 AND VP1 (RAV) homologs controlling juvenility and seasonal flowering in loquat. The expressions of EjRAV1/2 were relatively high during the juvenile or vegetative phase and low at the adult or reproductive phase. Overexpression of the two EjRAVs in Arabidopsis prolonged (about three-fold) the juvenile period by repressing the expressions of flowering activator genes. Additionally, the transformed plants produced more lateral branches than the wild type plants. Molecular assays revealed that the nucleus localized EjRAVs could bind to the CAACA motif of the promoters of flower signal integrators, EjFT1/2, to repress their expression levels. These findings suggest that EjRAVs play critical roles in maintaining juvenility and repressing flower initiation in the early life cycle of loquat as well as in regulating seasonal flowering. Results from this study not only shed light on the control and maintenance of the juvenile phase, but also provided potential targets for manipulation of flowering time and accelerated breeding in loquat.